Analysis of compensation cost related to musculoskeletal disorders (MSDs) against younger and older Malaysian manufacturing workers - Rohani, J. M. (IEOM Society, 2016)
This study analyzes compensation cost paid by the Social Security Organization of Malaysia (SOCSO) to the Malaysian manufacturing workers due to MSD related cases. The study compares MSD related cases based on three categories: cause of accident, type of injury and location of body injury against "older" workers and "younger" workers and gender differences. This study adopted top-down approach which utilized national statistics related to MSD claims data provided by SOCSO. The claim data is limited to MSD reported cases from 2009 to 2014. A total of 537 claims which related to MSD has been recorded in Malaysia within that period. The highest number of cases based on cause of accident is due to strenuous movement with average compensation cost at RM 28 400 (male younger workers) and RM 22 738 (male older workers). Besides, most of the claimants sustain MSD injury at the back body region. with average compensation cost of RM 28 117 (male younger workers) and RM 21 941 (male older workers). As for type of injury, sprains and strains recorded the highest number of cases with average compensation cost at RM 27 683 (male younger workers) and RM 23 875 (male older workers). This study will provide basis for future studies in MSD related injuries in working environment in Malaysia.